2008
DOI: 10.1002/pola.22526
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic oligomer chemistry

Abstract: Cyclic oligomers of engineering plastics such as polycarbonate and aromatic polyesters have been known for some time, being formed at very low levels during commercial manufacture. At GE Global Research, we have devised methods for high-yielding and selective preparation of such cyclic oligomers, that are amenable to commercial manufacture. The mixtures of cyclic oligomers have melting points significantly lower than individual ring sizes, and have very low viscosities in the melt. Ring-opening polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 32 publications
2
99
0
2
Order By: Relevance
“…However, several authors reported that their polymerizations at 250 C (30 min) yielded an equilibrium containing only small amounts (around 1 wt %) of cyclic oligomers, but without presenting compelling evidence for total equilibration. 194,195,199 Other authors presented their polymerizations as kinetically-controlled ROPs despite higher temperatures (up to 340 C). [196][197][198][199][200][201][202][203] For most entropy-driven ROPs, the question of kinetic or thermodynamic control was not discussed.…”
Section: Ring-ring Equilibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several authors reported that their polymerizations at 250 C (30 min) yielded an equilibrium containing only small amounts (around 1 wt %) of cyclic oligomers, but without presenting compelling evidence for total equilibration. 194,195,199 Other authors presented their polymerizations as kinetically-controlled ROPs despite higher temperatures (up to 340 C). [196][197][198][199][200][201][202][203] For most entropy-driven ROPs, the question of kinetic or thermodynamic control was not discussed.…”
Section: Ring-ring Equilibrationmentioning
confidence: 99%
“…206 Most of these ROPs were summarized in recent review articles. 199,203,204 ROPs of cyclic oligomeric bisphenol-A carbonate were most intensively studied. However, several authors reported that their polymerizations at 250 C (30 min) yielded an equilibrium containing only small amounts (around 1 wt %) of cyclic oligomers, but without presenting compelling evidence for total equilibration.…”
Section: Ring-ring Equilibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing attention is being paid recently to the utilization of cyclic oligoesters as feedstock for the synthesis and processing of aromatic polyesters [3,[7][8][9]. One source of cyclic oligoesters of great interest is cyclo-depolymerization of linear polyesters, which in combination with ROP, would provide an environmentally friendly route for the chemical recycling of currently important thermoplastics as poly(ethylene terephthalate) (PET), poly(butylene terephthalate) (PBT) and other closely related industrial aromatic polyesters and copolyesters [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A valuable up-dated account of the synthesis and polymerization of cyclic oligoesters has recently been reported by Brunelle. [26] PET is a classical engineering thermoplastic that is produced in huge amounts to be used mainly as fiber and in blowing-injection molding. New tendencies that point toward PET copolyesters with modified properties are able to satisfy new market demands.…”
Section: Introductionmentioning
confidence: 99%